Estudo de primeiros princípios da estabilidade e funcionalização da superfície e nanofitas de carbeto de silício - Rosso, Eduardo Fuzer (2014)
We use first principles calculations based upon the density functional theory to investigate the stability, geometry, electronic and magnetic properties of cibic silicon carbide (SiC) surfaces aligned along the (001) direction (β−SiC(001)) and nanoribbons (SiCNRs). The β−SiC(001) can be terminated in C or Si. For both terminations a great number of possible reconstruction are studied. To study the stability of the β−SiC(001) surface the formation energy is calculated, which shows that the two terminations (C or Si) have similar stability. Surfaces states are find in the bandgap for the two possible terminations. These surfaces states rule the electronic properties of the β−SiC(001) surface, which present metallic or semiconductor characteristics depending on the surface reconstruction. Aiming to saturate the dangling bonds and functionalize the C terminated β− SiC(001) surface, H atoms are adsorbed in the most stable configuration: the β− SiC(001) in the c(2x2) reconstruction where there are C dimers aligned in row and column. First we observe that the H adsorption is exothermic, indicating to a greater stability of the β−SiC(001) surface. Increasing the number of adsorbed H atoms (up to the third layer) we observe the formation of a nanotunnel structure. There tunnels are stable and small cavities present in the subsurface of the β−SiC(001). The semiconductor character of the β−SiC(001) in the presence of nanotunnels is preserved. The top of the valence band and of the boton of the band are surface states localized in hydrogenated C dimers near to the nanotunnel. Adsorbing Fe atoms on the β−SiC(001) surface we observe that the electronic and magnetic properties of the β−SiC(001) surface are strongly modified. There is a strong magnetic moment localized in Fe atoms adsorbed on the β−SiC(001) surface, which can present metallic or half metallic characteristics. The antiferromagnetic (AFM) interaction between the magnetic moments is favorable when compared to the ferromagnetic (FM) interaction. The electronic and magnetic properties of SiCNRs depend on the border structure. The SiCNRs terminated by H atoms and with armchair borders are semiconductor and no magnetic. Whereas the electronic and magnetic properties of SiCNRs terminated by H atoms and with zigzag border depend on the ribbon width and can be metallic or semiconductor. For pristine zigzag SiCNRs, the ferrimagnetic interaction between the borders is the ground state. The adsorption of Fe (atom and dimer) on a SiC sheet give rise to new electronic levels inside the bandgap and lead the SiC sheet to shows magnetic properties. The magnetic moment for Fe adsorbed on a SiC sheet is 2 μB and 6 μB, for a Fe atom or dimer adsorbed, respectively. The adsorption of Fe structures (atoms and dimers) on the SiCNRs is more stable near the borders of the ribbon. Depending on the Fe coverage and the magnetic interactions we can obtain, metallic, half-metallic, semiconductor or even a spin gapless semiconductor (SGS). These results show that functionalized SiC nanostructures are important materials for nanodevices.